Food industry digitalization: from challenges and trends to opportunities and solutions. Issue 11 (2018) - Demartini, Melissa; Pinna, Claudia; Tonelli, Flavio; Terzi, Sergio; Sansone, Cinzia; Testa, Chiara
Abstract: Over the last years, manufacturing companies have to face several challenges, mainly related to the volatility of the demand and to the continuously changing requirements, both from the customers and suppliers. In the meantime, new technological roadmaps and suggested interventions in manufacturing systems have been implemented. These solutions aim to exploit the high innovation and economic potential resulting from the continuing impact of rapidly advancing information and communication technology (ICT) in industry. This paper explores these topics focusing on the food sector. Indeed, companies belonging to this industry are facing global challenges, which can be met with the support of the information technologies (IT). The overall goal of this study is to help food companies toward digitalization, with a particular focus on the design and manufacturing processes. From the methodological point of view, Case Study has been used as research method. Furthermore, a questionnaire characterized by the different elements of the Manufacturing Value Modelling Methodology (MVMM) has been developed and used to gather information from companies. A framework for the digitalization process in the food industry has been developed basing on the results of a preliminary literature review and of different focus groups. On completion of the aforementioned framework, a list of enabling technologies has been discussed. These represent the technological solutions for the specific food issues highlighted by the framework. Finally, a case study has been accomplished in order to test and validate the contents' framework.